The ergogenic effects of acute carbohydrate feeding on resistance exercise performance: a systematic review and meta-analysis - King, A.; Helms, E.; Zinn, C.; Jukic, I (Sports Medicine, 2022)
Background: Carbohydrate (CHO) ingestion has an ergogenic effect on endurance training performance. Less is known about the effect of acute CHO ingestion on resistance training (RT) performance and equivocal results are reported in the literature. Objective: The current systematic review and meta-analysis sought to determine if and to what degree CHO ingestion influences RT performance. Methods: PubMed, MEDLINE, SportDiscus, Scopus, and CINAHL databases were searched for peer-reviewed articles written in English that used a cross-over design to assess the acute effect of CHO ingestion on RT performance outcomes (e.g., muscle strength, power, and endurance) in healthy human participants compared to a placebo or water-only conditions. The Cochrane Collaboration`s risk of bias tool and GRADE approaches were used to assess risk of bias and certainty of evidence, respectively. Random effects meta-analyses were performed for total training session volume and post-exercise blood lactate and glucose. Sub-group meta-analysis and meta-regression were performed for categorical (session and fast durations) and continuous (total number of maximal effort sets, load used, and CHO dose) covariates, respectively. Results: Twenty-one studies met the inclusion criteria (n = 226 participants). Pooled results revealed a significant benefit of CHO ingestion in comparison to a placebo or control for total session training volume (standardised mean difference [SMD] = 0.61). Sub-group analysis revealed a significant benefit of CHO ingestion during sessions longer than 45 min (SMD = 1.02) and after a fast duration of 8 h or longer (SMD = 0.39). Pooled results revealed elevated post-exercise blood lactate (SMD = 0.58) and blood glucose (SMD = 2.36) with CHO ingestion. Meta-regression indicated that the number of maximal effort sets, but not CHO dose or load used, moderates the effect of CHO ingestion on RT performance (beta co-efficient [b] = 0.11). Carbohydrate dose does not moderate post-exercise lactate accumulation nor do maximal effort sets completed, load used, and CHO dose moderate the effect of CHO ingestion on post-exercise blood glucose. Conclusions: Carbohydrate ingestion has an ergogenic effect on RT performance by enhancing volume performance, which is more likely to occur when sessions exceed 45 min and where the fast duration is = 8 h. Further, the effect is moderated by the number of maximal effort sets completed, but not the load used or CHO dose. Post-exercise blood lactate is elevated following CHO ingestion but may come at the expense of an extended time-course of recovery due to the additional training volume performed. Post-exercise blood glucose is elevated when CHO is ingested during RT, but it is presently unclear if it has an impact on RT performance. Protocol Registration: The original protocol was prospectively registered on the Open Science Framework (Project identifier: https://doi.org/10.17605/OSF.IO/HJFBW).